ANALISIS PENGARUH DAYA TARIK IKLAN DAN SELEBRITI ENDORSER PADA PROMO AdaAQUA TERHADAP MINAT BELI AMDK MEREK AQUA DENGAN CITRA MEREK SEBAGAI VARIABEL INTERVENING (Studi Kasus pada Mahasiswa S1 di Jawa Tengah dan DIY) - Anggi, Venny Faradika; Soesanto, Harry (Diponegoro Journal of Management, 2016)
This study aimed to analyze the influence of advertising appeal and celebrity endorser in the AdaAQUA promotion to purchase intention of AQUA using brand image as mediator. Simple random sampling method is used for this research. Samples were collected from 153 respondents who watch AdaAQUA promo's ads on TV. Multiple regression analysis is used for this study. The results showed that the advertising appeal has positive and significant effect to brand image, celebrity endorser has positive effect to brand image, advertising appeal has positive to purchase intention, celebrity endorser and brand image have positive and significant effect on purchase intention.